Poverty Reduction and Growth Trust : Borrowing Agreement with the Bank of Italy. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
On April 18, 2011, the Fund, as Trustee of the Poverty Reduction and Growth Trust (PRGT), entered into a borrowing agreement (the 'Agreement') with the Bank of Italy, by which Italy will provide new loan resources of up to SDR 800 million (see attachment). With this Agreement, the Fund has concluded eleven new borrowing agreements providing total resources of SDR 8,461 million in the context of the current fund-raising effort, which supports the reform of the Fund's lending facilities for low-income countries that became effective on January 7, 2010.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Agreement; Borrowing Agreement; Fund; PP; SDR; Italy